Towards systematic understanding of institutional interests in current agenda items at the world radiocommunication conference - Nattawut Ard-Paru (International Telecommunications Society (ITS), 2011)
The World Radiocommunication Conference (WRC) serves as a forum to negotiate, review, and revise the Radio Regulations (RR), an international treaty and one of the most difficult regulations for radiocommunication services. RR is complex since it includes intergovernmental issues in relation to regulation covering technical, legal and societal aspects. A large number of parties are interested and involved in revising RR and creating supranational instruments for optimal management of the spectrum. As a consequence, it can be difficult for one involved stakeholder to see its own position and other relevant issues directly influencing them in relation to the whole work of WRC and its subprocesses. A systematic analysis of the main decision-making process would contribute to better understanding of the role of WRC and positions of the involved parties. The aim of the paper is to contribute to better understanding of the role of the WRC with a focus on the current agenda items. Agenda items are specified issues from RR that need to be handled at an actual conference. The point of departure is using the institutional analysis and development (IAD) framework [see Ostrom (2011)] to gain a suitable institutional overview of the main decision-making process and its sub-processes. The IAD framework has the capacity to explain jointly produced outcomes, such as negotiating an international treaty depending on multiple inputs and different priority levels. Also, it can be used to enhance the understanding of WRC matters in order to improve the decision-making process by focusing on the main interactions and involved parties in relation to the possible outcomes of the WRC. The paper is based on data obtained from historical documents, content analysis, literature review, observations, and interviews. The results of this paper illustrate the benefits of the IAD framework in the context of the WRC, especially for the process of agenda setting and study cycles. The practical implications are important for policy makers, for example, since it highlights critical actors, events, and interactions aligned with the main activities of WRC. A stakeholder will better understand its own position and its possibility for control, both in relation to the overall process and the sub-processes important for agenda items in which it has an interest. It will gain understanding not only of the overall role of WRC, but also of its own possibilities to intervene during the process of revision of RR so that it could protect its interests - e.g., with more proper contribution in the suitable forums with the expected outcome.
Keywords: Y40; 330; Radio Regulations (RR); institutional analysis and development (IAD) framework; World Radiocommunication Conference (WRC); WRC agenda items; decision situation